The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1111/1753-0407.12019
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Ethnomedical Claim III: Anti‐hyperglycemic activities of Gongronema latifolium root and stem (民族药物需求评估III:Gongronema latifolium根与茎的降糖活性)

Abstract: The results confirm pancreatic activity as a mechanism underlying the antidiabetic action of G. latifolium and justify its ethnomedical use.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…A significant (p < 0.05) time-dependent hyperglycaemia-lowering effects up to the fourth hour was observed in the negative control group of rats that were given normal saline. This activity could be attributed to the normal homeostatic regulatory mechanism in normal animals which confirmed the healthy state of the pancreases of the animals used in the study [20][21][22][23]. Also, the positive control group of rats that were administered with glibenclamide(5 mg/kg) gave a significant time-dependent antihyperglycaemic activity up to fourth hour (Table 1).…”
Section: Antihyperglycaemic Effects Of the Extractsupporting
confidence: 57%
See 2 more Smart Citations
“…A significant (p < 0.05) time-dependent hyperglycaemia-lowering effects up to the fourth hour was observed in the negative control group of rats that were given normal saline. This activity could be attributed to the normal homeostatic regulatory mechanism in normal animals which confirmed the healthy state of the pancreases of the animals used in the study [20][21][22][23]. Also, the positive control group of rats that were administered with glibenclamide(5 mg/kg) gave a significant time-dependent antihyperglycaemic activity up to fourth hour (Table 1).…”
Section: Antihyperglycaemic Effects Of the Extractsupporting
confidence: 57%
“…The antihyperglycaemic assay of the extract, A and its partition fractions, B1-B4 were carried out in glucose-induced hyperglycaemic normal rats as described by Adebajo, Ayoola and their co-workers [20][21][22][23].…”
Section: Antihyperglycaemic Assay Of the Extract Fractionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Examples of these are triterpenes such as α-amyrin-3O-β-(5-hydroxy) ferulic acid, terpenoids, sesquiterpenoids and sesquiterpene. These molecules have been suggested to potentiate their anti-diabetic activity through the stimulation of insulin secretion [ 45 , 127 ]. Hence, isolation of terpenes for anti-diabetic activities could be directed toward the potentiation of insulin secretion of the pancreas.…”
Section: Resultsmentioning
confidence: 99%
“…Previous report revealed that prevalence of DM in Nigeria has increased from 2.2% in 1997 to 5.0% by 2013 [4]. The high costs and adverse effects of insulin and therefore the available oral hypoglycaemic agents have necessitated increased investigations on medicinal plants used ethnomedically for the management of diabetes [8][9]. According to the WHO, over 80% of the world's population depend upon traditional sorts of medicine, largely plant based to satisfy primary health care needs [18].…”
Section: Introductionmentioning
confidence: 99%